FRI0326 Effectiveness and safety of etanercept in paediatric subjects with extended oligoarticular juvenile idiopathic arthritis, enthesitis-related arthritis, or psoriatic arthritis: The clipper study. (23rd January 2014) - Horneff, G.; Ruperto, N.; Burgos-Vargas, R.; Panaviene, V.; Alvarez, D.; Zang, C.; Wajdula, J.; Woodworth, D.; Vlahos, B.; Martini, A.
Abstract : Background: Limited information is available on the effects of etanercept (ETN) on the juvenile idiopathic arthritis (JIA) subtypes, extended oligoarticular JIA (eoJIA), enthesitis-related arthritis (ERA), and psoriatic arthritis (PsA). Objectives: To assess the efficacy and safety of ETN in paediatric subjects with eoJIA, ERA, and PsA. Methods: CLIPPER is an ongoing, Phase 3b, open-label, multi-centre study; the primary analyses (12-week data) are reported here. Subjects with eoJIA (2–17 y old), ERA (12–17 y old), or PsA (12–17 y old) received ETN 0.8 mg/kg once weekly (max. dose 50 mg). Endpoints included the percentage of subjects achieving American College of Rheumatology (ACR) Paediatric 30 (primary endpoint) and 50/70/90/100 criteria at Week 12. Logistic regression analysis was used to compare the ACR Paediatric 30 data with historical placebo data from a meta-analysis of JIA studies [1] and a juvenile-onset spondyloarthropathy study [2]. Results: 127 subjects (mean age 11.7 y) received ≥1 dose of ETN; 5 (3.9%) subjects discontinued the study. Concomitant disease-modifying anti-rheumatic drugs, corticosteroids, and non-steroidal anti-inflammatory drugs were received by 109 (85.8%), 16 (12.6%), and 74 (58.3%) subjects, respectively. ACR Paediatric 30/50/70/90/100 response rates (Tables 1 and 2 ) were similar across all JIA subtypes. Odds ratios for ACR Paediatric 30 showed a significant advantage of ETN over the historical placebo data. Treatment-emergent adverse events (TEAEs), treatment-emergent infections, serious TEAEs, and malignancies were reported in 45 (35.4%), 58 (45.7%), 4 (3.1%), and 0 (0.0%) subjects, respectively. Serious TEAEs were 1 (0.8%) case each of abdominal pain, bronchopneumonia, gastroenteritis, and pyelocystitis. One (0.8%) subject reported an opportunistic infection of herpes zoster. No clinically meaningful differences in safety were observed across the JIA subtypes. Conclusions: Etanercept treatment for 12 weeks was effective in treating subjects with the JIA subtypes, eoJIA, ERA, or PsA, with no unexpected safety findings. References: Ruperto N, et al. Arthritis Rheum 2003;48(Suppl 9):S90. Burgos-Vargas R, et al. Ann Rheum Dis 2008;67(Suppl 2):69. Disclosure of Interest: G. Horneff Grant/Research support from: Abbott, Pfizer Inc., Wyeth., N. Ruperto Grant/Research support from: Abbott, AstraZeneca, Bristol-Myers Squibb, Centocor Research and Development, Eli Lilly and Co., "Francesco Angelini" s.p.a., GlaxoSmithKline, Italfarmaco, Merck Serono, Novartis, Pfizer Inc., Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Wyeth, Xoma, Speakers Bureau: AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Novartis, Roche, R. Burgos-Vargas Grant/Research support from: Abbott, Consultant for: Abbott, Bristol-Myers Squibb, Janssen, Pfizer Inc., Roche, Speakers Bureau: Abbott, Bristol-Myers Squibb, Janssen, MSD, Pfizer Inc., Roche, V. Panaviene: None Declared, D. Alvarez Employee of: Pfizer Inc., C. Zang Employee of: Pfizer Inc., J. Wajdula Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., D. Woodworth Employee of: Pfizer Inc., B. Vlahos Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., A. Martini Grant/Research support from: Abbott, AstraZeneca, Bristol-Myers Squibb, Centocor Research and Development, Eli Lilly and Co., "Francesco Angelini" s.p.a., GlaxoSmithKline, Italfarmaco, Merck Serono, Novartis, Pfizer Inc., Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Wyeth, Xoma, Speakers Bureau: AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Novartis, Roche